Synthesis and characterization of biodegradable pH and reduction dual‐sensitive polymeric micelles for doxorubicin delivery. Issue 13 (15th April 2014) - Chu, Yanfeng; Yu, Huan; Ma, Yingying; Zhang, Yunti; Chen, Weihai; Zhang, Guangyan; Wei, Hua; Zhang, Xianzheng; Zhuo, Renxi; Jiang, Xulin
ABSTRACT Novel pH and reduction dual‐sensitive biodegradable polymeric micelles for efficient intracellular delivery of anticancer drugs were prepared based on a block copolymer of methyloxy‐poly(ethylene glycol)‐b‐poly[(benzyl‐l‐aspartate)‐co‐(N‐(3‐aminopropyl) imidazole‐l‐aspartamide)] [mPEG‐SS‐P(BLA‐co‐APILA), MPBA] synthesized by a combination of ring‐opening polymerization and side‐chain reaction. The pH/reduction‐responsive behavior of MPBA was observed by both dynamic light scattering and UV–vis experiments. The polymeric micelles and DOX‐loaded micelles could be prepared simply by adjusting the pH of the polymer solution without the use of any organic solvents. The drug release study indicated that the DOX‐loaded micelles showed retarded drug release in phosphate‐buffered saline at pH 7.4 and a rapid release after exposure to weakly acidic or reductive environment. The empty micelles were nontoxic and the DOX‐loaded micelles displayed obvious anticancer activity similar to free DOX against HeLa cells. Confocal microscopy observation demonstrated that the DOX‐loaded MPBA micelles can be quickly internalized into the cells, and effectively deliver the drugs into nuclei. Thus, the pH and reduction dual‐responsive MPBA polymeric micelles are an attractive platform to achieve the fast intracellular release of anticancer drugs. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1771–1780